New developments in simulation–based harbour crane training. (18th July 2012) - García–FernÁ?ndez, Ignacio; Pla–Castells, Marta; Gamón, Miguel A.; Martínez–DurÁ?, Rafael J.
This paper presents the efforts that have been made during the development of a set of harbour training simulators to improve their quality. The paper focuses on two main research lines: the improvement of complex physical systems involved in the simulation and the analysis of hardware architecture solutions. Cable–based hoist systems and bulk materials are systems present in different harbour equipment and are usually simulated with poor quality due to their complexity. In this paper physics–based models for the interactive simulation of these systems are proposed and applied to real cases. Also, different hardware simulator architectures are analysed and different approaches are proposed to the problem of choosing the devices for a simulator.